Direct Synthesis of Enones by Visible-Light-Promoted Oxygenation of Trisubstituted Olefins Using Molecular Oxygen - Harada, Shinji; Matsuda, Daiki; Morikawa, Takahiro; Nishida, Atsushi (Synlett, 2020)
A one-step synthesis of enones from olefins is described. The reaction was performed under visible-light irradiation in the presence of molecular oxygen and a photocatalyst. The reaction proceeded with various types of trisubstituted olefins to give enones in good yields with high regioselectivity. In particular, oxygen- and nitrogen-containing functional groups, heteroaromatic rings, and cyclopropanes were tolerated. Mechanistic studies and previous reports indicated that the active oxygen species generated in the reaction system is singlet oxygen.
Keywords: oxidation; oxygenation; photocatalysis; ruthenium catalysis; enones; alkenes